Menyiapkan Generasi Z yang Berkarakter dan Bijak Dalam Penggunaan Teknologi Melalui Pendidikan - Annisa Maharani; Miftahur Rahmah; Reysha Fadzilah Anisha; Ardi Ardi (Peneliti.net, 2023)
The development of the times has entered the era of generation Z which is synonymous with technology generation. Generation Z are children born in 1998-2009 who are currently still in school. To prevent generation Z from being affected by the negative impact of using technology, character education is needed. The method used in this article is a literature review. The results of the discussion show that the use of technology in the educational process needs to be accompanied by character education to prepare Generation Z with character and wisdom in using technology. The achievement of this character education goal requires the role of schools as educational institutions and teachers as school managers to set an example in using technology.